The Influence of Completion of Independent Training and Teacher Competency Reflection Scores on Elementary Students’ National Assessment Results - Bari, Saiful; Suryani, Nunuk; Indriayu, Mintasih; Setyowibowo, Feri (Universitas Sebelas Maret, 2025)
The Merdeka Mengajar platform is a strategic initiative of the Ministry of Education, Culture, Research, and Technology of Indonesia, aimed at enhancing teacher competencies through self-directed learning and reflective assessment. Two key features of this platform, Independent Training (Pelatihan Mandiri) and Competency Reflection (Refleksi Kompetensi, Refkom), are designed to support teachers’ professional development in a flexible and needs-based manner. This study examines the influence of Independent Training completion and Refkom scores on elementary students’ performance in the 2023 National Assessment (Asesmen Nasional), covering literacy, numeracy, and character domains. The research population comprises elementary school teachers who participated in online Independent Training programs in 2022. Data were analyzed using linear regression, with school accreditation status included as a control variable. The results indicate that students taught by teachers who completed the Independent Training achieved significantly higher literacy and numeracy scores. Teachers’ Refkom scores also had a positive effect on students’ numeracy outcomes, although the relationship was not significant for character development. These findings suggest that strengthening teacher competencies through Independent Training and Refkom contributes meaningfully to improving the quality of student learning.